Monatomic Ir-loaded Co3O4 material, preparation method and application

By loading single-atom Ir on Co3O4 material, a single-atom Ir loaded Co3O4 material with high stability and high chlorine activity is prepared, which solves the problems of high consumption and high cost of electrocatalysts in existing chlorine production and provides a low cost The new anode catalyst is better than commercial DSA catalysts.

CN119121310APending Publication Date: 2024-12-13HUAZHONG NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310700123.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-13
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The current electrocatalyst consumption and costly in the production of chlorine are high, which limits the widespread application of seawater chlorine, and the high load of precious metals, which limits the promotion of catalysts in other fields.

Method used

By loading single-atom Ir on the Co3O4 material, using a simple two-shot electrodeposition and high-temperature heating process, a single-atom Ir-loaded Co3O4 material with high stability and high chlorine activity was prepared for electrochemical chlorine analysis reaction.

Benefits of technology

It improves the chlorine evolution activity and stability of chlorine, reduces the amount and cost of precious metals, and provides a new anode catalyst with low metal loading and low cost, which is better than commercial DSA catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121310A_ABST
    Figure CN119121310A_ABST
Patent Text Reader

Abstract

The invention discloses a monatomic Ir loaded Co3O4 material as well as a preparation method and application thereof. The monatomic Ir-loaded Co3O4 material with high stability and high chlorine evolution activity is prepared through simple processes such as two times of electrodeposition, high-temperature heating and the like. The monatomic Ir-loaded Co3O4 material provided by the invention has oxygen vacancies and is of a uniform nanosheet array structure, Ir is in a monatomic form and is uniformly distributed on Co3O4 nanosheets, and the monatomic Ir-loaded Co3O4 material is used for electrochemical chlorine production, is good in chlorine production performance and has excellent stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of semiconductor nanomaterials, and in particular to a single-atom Ir-loaded Co3O4 composite material, a preparation method and an application thereof. Background Art

[0002] There are a large number of chemicals used for disinfection on the market. The most common chemicals used for disinfection are chlorine, chlorine dioxide and hypochlorite. As a chemical precursor, chlorine (Cl2) has a very wide range of uses. It is mainly used as a strong oxidant, industrial bleaching, sterilization and disinfection, pharmaceuticals and wastewater treatment, etc. It also plays a vital role in many important industrial processes. In recent years, my country's chlorine production has increased year by year. According to statistics, as of 2019, my country's chlorine production was 30.6961 million tons. In industry, chlorine production widely relies on the chlor-alkali process, which uses saturated NaCl to produce chlorine. This not only increases costs, but also seriously hinders the widespread application of electrocatalysis in chlorine production. On the contrary, seawater is more competitive than fresh water in economic terms.

[0003] At present, people have been working hard to develop efficient catalysts as electrocatalysts for chlorine production from seawater, and various strategies have been proposed. During the chlorine production process, the electrocatalyst consumes 60% of the electricity, which indicates that the chlorine production efficiency is affected by the catalytic performance of the chlorine evolution reaction catalyst on the anode. After many studies and improvements, the two catalysts, dimensionally stable anode (DSA) and Ti-supported IrO2 / RuO2, have become the first choice for chlorine evolution reaction. DSA usually shows very high selectivity for chlorine evolution reaction. Although the durability of DSA is extremely high, which can reach several years or even ten years, the cost of DSA is extremely high. Although the two catalysts IrO2 / RuO2 have excellent chlorine evolution performance, the large use of precious metals limits their promotion in other fields. Therefore, it is necessary to propose a new anode catalyst with low metal loading, low cost and low overpotential.

[0004] The present invention improves the chlorine evolution activity by loading single-atom Ir on Co3O4 material, and prepares single-atom Ir loaded Co3O4 material with high stability and high chlorine evolution activity through simple processes such as two-time electrodeposition and high-temperature heating. Summary of the invention

[0005] The invention aims to provide single-atom Ir-loaded Co3O4 material, preparation method and application in view of the deficiencies in the prior art. The single-atom Ir-loaded Co3O4 material provided by the invention can be used for electrochemical chlorine evolution, has good chlorine production performance and excellent stability.

[0006] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is:

[0007] The first aspect of the present invention provides a single-atom Ir-loaded Co3O4 material having oxygen vacancies and a uniform nanosheet array structure, wherein Ir is in the form of a single atom and is uniformly distributed on the Co3O4 nanosheet.

[0008] According to the above scheme, the Ir loading is 1 to 1.5%.

[0009] The second aspect of the present invention provides a method for preparing a single-atom Ir-loaded Co3O4 material, which uses a cobalt nitrate solution as an electrolyte, immerses a carrier as an electroplated substrate in the cobalt nitrate solution, and uses an electrochemical workstation to select an Amperometric Curve to deposit Co(OH)2 on the carrier at a constant potential; immerses the carrier on which Co(OH)2 is deposited, which is obtained above, in an iridium trichloride solution, and uses an electrochemical workstation to select a CV method (Cyclic Voltammetry), and performs electrochemical treatment to obtain Co(OH)2 loaded with Ir, wherein the voltage range is 0.3 to -1 V, and the number of stages is 20 to 80 stages; finally, the Co(OH)2 loaded with Ir is calcined to obtain the single-atom Ir-loaded Co3O4 material of the present invention.

[0010] According to the above scheme, the concentration of the cobalt nitrate solution is 0.025-0.05M; the concentration of the iridium trichloride solution is 50-200μM.

[0011] According to the above scheme, the carrier is a titanium mesh, a titanium sheet or a carbon paper.

[0012] According to the above scheme, the carrier is a titanium mesh, and the processing method of the titanium mesh is: the titanium mesh is subjected to acetone and ethanol water ultrasonic treatment for dust removal and organic matter removal in turn, each ultrasonic treatment lasts for 10 to 15 minutes, and then it is washed and dried alternately with water and ethanol before deposition.

[0013] According to the above scheme, the voltage of constant potential deposition is set to -0.8 to -1.2 V, and the deposition time is 4 to 10 minutes.

[0014] According to the above scheme, the counter electrode of the constant potential deposition and CV electrochemical treatment is a platinum mesh, and the reference electrode is a saturated calomel electrode. After the reaction is completed, water and ethanol are alternately washed and blown dry.

[0015] According to the above scheme, the CV deposition calcination is more preferably 30-50 stages.

[0016] According to the above scheme, the calcination temperature is 250-400°C and the calcination time is 2-4h.

[0017] According to the above scheme, the calcination heating rate is 2 to 5°C / s.

[0018] The third aspect of the present invention provides the use of the above-mentioned single-atom Ir-loaded Co3O4 material as an anode in an electrochemical chlorine production reaction.

[0019] According to the above scheme, the electrolyte in the electrochemical chlorine production reaction is a NaCl solution.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. The Ir@Co3O4 material provided by the present invention has more active sites, and the oxygen vacancy structure can accelerate the transfer and transmission of photogenerated charge carriers. Compared with Co3O4, the doping of Ir can reduce the binding energy of chlorine, which is beneficial to the desorption of Cl· and improves the electronic activity of the Co site; the catalyst structure is stable during the chlorine evolution process and has excellent stability.

[0022] 2. The present invention first obtains Co(OH)2 by constant voltage deposition using the IT method; then deposits Ir single atoms on Co(OH)2 using the CV method with a voltage of 0.3 to -1V and 20 to 80 CV stages; finally, calcination is performed to prepare Ir-loaded Co3O4 material with oxygen vacancies. The synthesis method is simple, the amount of precious metals used is small, and the cost is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a scanning electron microscope (SEM) photograph of Ir@Co3O4 prepared by the present invention.

[0024] Figure 2 This is a spherical aberration corrected transmission electron microscope (AC-TEM) picture of Ir@Co3O4 prepared by the present invention.

[0025] Figure 3 This is a scanning electron microscope (SEM-mapping) photograph of Ir@Co3O4 prepared by the present invention.

[0026] Figure 4 This is an electron paramagnetic resonance (EPR) image of Ir@Co3O4 prepared by the present invention.

[0027] Figure 5 It is a comparison chart of chlorine evolution performance of Ir@Co3O4 prepared by the present invention with different deposition times.

[0028] Figure 6 It is an X-ray diffraction (XRD) diagram of Ir@Co3O4 prepared by the present invention.

[0029] Figure 7 This is a Raman diffraction (Raman) diagram of Ir@Co3O4 prepared by the present invention, wherein line a is the Raman characterization of Ir@Co3O4 before the chlorine evolution reaction, and line b is the characterization when the chlorine evolution reaction reaches a high potential (1.5V).

[0030] Figure 8 The chlorine evolution activity performance of Ir@Co3O4 and Co3O4 prepared by the present invention is shown, wherein the counter electrode is a platinum electrode and the reference electrode is Ag / AgCl. Curve a is Ir@Co3O4 and curve b is Co3O4. Co3O4 is the product of step 2 and is obtained directly through step 5 without going through steps 3 and 4. DETAILED DESCRIPTION

[0031] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0032] The chemical reagents used in the present invention are cobalt nitrate hexahydrate, iridium trichloride and potassium hydroxide.

[0033] Embodiment 1:

[0034] Step 1: Weigh 0.182 g of cobalt nitrate hexahydrate, add 25 ml of deionized water, and ultrasonicate at room temperature for 3 min until it is completely dissolved and the solution is light pink.

[0035] Step 2: Cut the titanium mesh into 1cm×0.5cm size, wash the treated titanium mesh with water and ethanol and blow dry, clamp it with an electrode clamp as a working electrode, and immerse it in the above cobalt nitrate solution. The counter electrode is a platinum mesh and the reference electrode is saturated calomel. Turn on the electrochemical workstation and set the voltage to -1V and the working time to 240s. After the end, wash it alternately with water and ethanol and blow dry to obtain sky blue Co(OH)2.

[0036] Step 3: Weigh 0.0149 g of iridium trichloride into a 1.5 ml centrifuge tube, add 1 ml of 1M KOH into the centrifuge tube, and shake the centrifuge tube until the solution is purple. Take 20 μL of the solution in the centrifuge tube into a 25 ml beaker, add 10 ml of 1M KOH into the beaker, and sonicate for 3 minutes to fully mix until the solution is light purple. The concentration of iridium trichloride is 100 μM.

[0037] Step 4: Clamp the titanium mesh with Co(OH)2 deposited above with an electrode clamp and immerse it in the above lavender solution as the working electrode, the counter electrode is a platinum mesh, and the reference electrode is a mercury oxide electrode. The electrochemical workstation selects CV, where the voltage range is 0.1 to -0.4V, the scan rate is 0.01V / s, and the number of segments is 40. After the end, wash it alternately with water and ethanol and blow dry it to obtain brown Ir-loaded Co(OH)2.

[0038] Step 5: Place the brown titanium mesh in a tubular furnace and heat it with an initial temperature of 30°C, a heating rate of 2°C / s, and a heating time of 135 min. Heat to 300°C and maintain at 300°C for 2 h to obtain a black Ir@Co3O4 product.

[0039] Embodiment 2:

[0040] Step 1: Weigh 0.182 g of cobalt nitrate hexahydrate, add 25 ml of deionized water, and ultrasonicate at room temperature for 3 min until it is completely dissolved and the solution is light pink.

[0041] Step 2: Cut the titanium mesh into 1cm×0.5cm size, wash the treated titanium mesh with water and ethanol and blow dry, clamp it with an electrode clamp as a working electrode, and immerse it in the above cobalt nitrate solution. The counter electrode is a platinum mesh and the reference electrode is saturated calomel. Turn on the electrochemical workstation and set the voltage to -0.8V and the working time to 240s. After the end, wash it alternately with water and ethanol and blow dry to obtain sky blue Co(OH)2.

[0042] Step 3: Weigh 0.0149 g of iridium trichloride into a 1.5 ml centrifuge tube, add 1 ml of 1M KOH into the centrifuge tube, and shake the centrifuge tube until the solution is purple. Take 20 μL of the solution in the centrifuge tube into a 25 ml beaker, add 10 ml of 1M KOH into the beaker, and sonicate for 3 minutes to fully mix until the solution is light purple. The concentration of iridium trichloride is 100 μM.

[0043] Step 4: Clamp the titanium mesh with Co(OH)2 deposited above with an electrode clamp and immerse it in the above lavender solution as the working electrode, the counter electrode is a platinum mesh, and the reference electrode is a mercury oxide electrode. The electrochemical workstation selects CV, where the voltage range is 0.1 to -0.4V, the scan rate is 0.01V / s, and the number of segments is 40. After the end, wash it alternately with water and ethanol and blow dry it to obtain brown Ir-loaded Co(OH)2.

[0044] Step 5: Place the brown titanium mesh in a tubular furnace and heat it with an initial temperature of 30°C, a heating rate of 2°C / s, and a heating time of 135 min. Heat to 300°C and maintain at 300°C for 2 h to obtain a black Ir@Co3O4 product.

[0045] Embodiment 3:

[0046] Step 1: Weigh 0.364 g of cobalt nitrate hexahydrate into a 25 ml beaker, add 25 ml of deionized water, and sonicate at room temperature for 3 min until all cobalt nitrate is dissolved and the solution is light pink.

[0047] Step 2: Cut the titanium mesh into 1cm×0.5cm size, wash the treated titanium mesh with water and ethanol and blow dry, clamp it with an electrode clamp as a working electrode, and immerse it in the above solution. The counter electrode is a platinum mesh and the reference electrode is saturated calomel. Turn on the electrochemical workstation and set the voltage to -1V and the working time to 240s. After the end, wash it alternately with water and ethanol and blow dry to obtain sky blue Co(OH)2.

[0048] Step 3: Weigh 0.0149 g of iridium trichloride into a 1.5 ml centrifuge tube, add 1 ml of 1 M KOH into the centrifuge tube, and shake the centrifuge tube until the solution turns purple. Take 20 μL of the solution in the centrifuge tube into a 25 ml beaker, add 10 ml of 1 M KOH into the beaker, and sonicate for 3 minutes to fully mix until the solution turns light purple.

[0049] Step 4: Clamp the titanium mesh with Co(OH)2 deposited above with an electrode clamp and immerse it in the above lavender solution as the working electrode, the counter electrode is a platinum mesh, and the reference electrode is a mercury oxide electrode. The electrochemical workstation selects CV, where the voltage range is 0.1 to -0.4V, the scan rate is 0.01V / s, and the number of segments is 40. After the end, wash it alternately with water and ethanol and blow dry it to obtain brown Ir-loaded Co(OH)2.

[0050] Step 5: Place the brown titanium mesh in a tubular furnace and heat it with an initial temperature of 30°C, a heating rate of 2°C / s, a heating time of 135 min, heating to 300°C, and a holding time of 2 h to obtain black Ir@Co3O4 as the final product.

[0051] Embodiment 4:

[0052] Step 1: Weigh 0.182 g of cobalt nitrate hexahydrate into a 25 ml beaker, add 25 ml of deionized water, and sonicate at room temperature for 3 min until all the cobalt nitrate is dissolved and the solution is light pink.

[0053] Step 2: Cut the titanium mesh into 1cm×0.5cm size, wash the treated titanium mesh with water and ethanol and blow dry, clamp it with an electrode clamp as a working electrode, and immerse it in the above solution. The counter electrode is a platinum mesh and the reference electrode is saturated calomel. Turn on the electrochemical workstation and set the voltage to -1V and the working time to 10min. After the end, wash it alternately with water and ethanol and blow dry to obtain sky blue Co(OH)2.

[0054] Step 3: Weigh 0.0149 g of iridium trichloride into a 1.5 ml centrifuge tube, add 1 ml of 1 M KOH into the centrifuge tube, and shake the centrifuge tube until the solution turns purple. Take 20 μL of the solution in the centrifuge tube into a 25 ml beaker, add 10 ml of 1 M KOH into the beaker, and sonicate for 3 minutes to fully mix until the solution turns light purple.

[0055] Step 4: Clamp the titanium mesh with Co(OH)2 deposited above with an electrode clamp and immerse it in the above lavender solution as the working electrode, the counter electrode is a platinum mesh, and the reference electrode is a mercury oxide electrode. The electrochemical workstation selects CV, where the voltage range is 0.1 to -0.4V, the scan rate is 0.01V / s, and the number of segments is 40. After the end, wash it alternately with water and ethanol and blow dry it to obtain brown Ir-loaded Co(OH)2.

[0056] Step 5: Place the brown titanium mesh in a tubular furnace and heat it with an initial temperature of 30°C, a heating rate of 2°C / s, a heating time of 135 min, heating to 300°C, and a holding time of 3 h to obtain black Ir@Co3O4 as the final product.

[0057] Embodiment 5:

[0058] The steps are the same as Example 1, except that the number of stages in step 4 is 20, 60, and 80 stages respectively, and the other reaction conditions remain unchanged.

[0059] Results Analysis

[0060] The Ir@Co3O4 materials prepared in Examples 1-5 were characterized by SEM, TEM, and AC-TEM. The present invention prepared single-atom Ir-loaded Co3O4 materials with oxygen vacancies and a uniform nanosheet array structure. Ir was in the form of single atoms and was uniformly distributed on the Co3O4 nanosheets.

[0061] The characterization results of the Ir@Co3O4 material prepared in Example 1 are specifically analyzed as follows. The Co3O4 material is a uniform nanosheet array on the surface of the carrier, as shown in the attached Figure 1 As shown. Ir exists in the form of a single atom, as shown in the attached Figure 2 The Ir single atoms are evenly distributed on the Co3O4 nanosheets, as shown in the attached Figure 3 The oxygen vacancies in Ir@Co3O4 are shown in the attached figure. Figure 4 .

[0062] The material prepared in combination with Example 5 was tested, as shown in the attached Figure 5 As shown in the figure, by comparing the material without CV deposition (line a), the deposition of a certain amount of Ir single atoms can improve the chlorine evolution performance of the material (CV deposition 20 segments, 40 segments, 60 segments, 80 segments). In comparison, when CV deposition is 40 segments (line c), the chlorine evolution performance is the best. The Ir loading has an impact on the chlorine evolution performance of the Ir@Co3O4 material. If the Ir loading is too low, the activity improvement is small. If the Ir loading is too high, it may replace too many Co active sites, which will affect the chlorine evolution performance of the Ir@Co3O4 material.

[0063] The prepared Ir@Co3O4 material was tested by XRD. Figure 6 As shown, the obtained diffraction peaks prove that the synthesized material is Co3O4 material.

[0064] The Ir@Co3O4 material prepared in Example 1 of the present invention was analyzed by inductively coupled plasma mass spectrometry (ICP-MS), and the results showed that the content of Ir was 1.05%.

[0065] Raman diffraction was used to analyze the Ir@Co3O4 material prepared by the present invention. Since the chlorine evolution reaction produces chlorine gas which is corrosive to the electrode material, most electrode materials have poor stability. Therefore, the stability test of the Ir@Co3O4 material prepared by the present invention was carried out. The results are shown in the attached figure. Figure 7 Line a is the characterization before the chlorine evolution reaction begins, and line b is the characterization result when the chlorine evolution reaction is carried out to a high potential (1.5V). It can be seen that under the high potential reaction, the peak does not shift and the material structure does not change. However, since the Co3O4 material is not doped with single-atom Ir, the Raman diffraction peak will shift significantly when the reaction is carried out to a high potential (1.5V), and the shift is 4.37cm -1 , which illustrates the strong stability of the Ir@Co3O4 material structure.

[0066] The specific steps of using the Ir@Co3O4 material prepared by the present invention to test the chlorine evolution anode reaction are as follows: 30 ml of 0.5M NaCl is installed on both sides of the electrochemical reaction cell, and the Ir@Co3O4 material is clamped with an electrode clamp as the working electrode, the counter electrode is a platinum mesh, and the reference is Ag / AgCl. The electrochemical workstation turns on LSV, the voltage is 0.8-1.4V, the scan rate is 0.005V / s, and the resistance is recorded. The chlorine evolution reaction test of other samples for comparison is similar to it, ensuring that the reaction area is the same. The results are shown in the attached figure. Figure 8 The results shown in the figure are curve a for Ir@Co3O4 and curve b for Co3O4. Ir@Co3O4 material at 70 mA cm -2 The anode potential under current density is reduced by 30mV. Compared with Co3O4, the chlorine production performance of Ir@Co3O4 material is significantly improved. The chlorine production performance of Ir@Co3O4 material prepared by the present invention is also significantly better than that of commercial DSA (commercial DSA is often used to precipitate chlorine in the laboratory). Commercial DSA has a chlorine production performance of 70mA cm -2 The anode potential under the current density is 1.3 V, which is 0.1 V higher than the anode potential of the Ir@Co3O4 material prepared by the present invention.

[0067] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

[0068] The above is only a preferred embodiment of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. Single-atom Ir-loaded Co3O4 material, characterized in that: It has oxygen vacancies and a uniform nanosheet array structure. Ir is in the form of single atoms and is evenly distributed on the Co3O4 nanosheets.

2. The single-atom Ir-loaded Co3O4 material according to claim 1, characterized in that: The Ir loading is 1 to 1.5%.

3. The method for preparing the single-atom Ir-loaded Co3O4 material according to claim 1, characterized in that: The method uses a cobalt nitrate solution as an electrolyte, immerses a carrier as an electrodeposition substrate in the cobalt nitrate solution, selects the current time method Amperometric it Curve on the electrochemical workstation, and deposits Co(OH)2 on the carrier at a constant potential; immerses the carrier deposited with Co(OH)2 obtained above in an iridium trichloride solution, selects the CV method on the electrochemical workstation, and performs electrochemical treatment to obtain Co(OH)2 loaded with Ir, wherein the voltage range is 0.3 to -1V, and the number of stages is 20 to 80; finally, the Co(OH)2 loaded with Ir is calcined to prepare the single-atom Ir-loaded Co3O4 material of the present invention.

4. The method for preparing the single-atom Ir-loaded Co3O4 material according to claim 3, characterized in that: The carrier is a titanium mesh, a titanium sheet or a carbon paper.

5. The method for preparing the single-atom Ir-loaded Co3O4 material according to claim 3, characterized in that: The concentration of the cobalt nitrate solution is 0.025-0.05M; the concentration of the iridium trichloride solution is 50-200μM.

6. The method for preparing the single-atom Ir-loaded Co3O4 material according to claim 3, characterized in that: The carrier is a titanium mesh, and the titanium mesh is treated by ultrasonic treatment of acetone and ethanol water to remove dust and organic matter in turn, each ultrasonic treatment lasts for 10 to 15 minutes, and then the titanium mesh is washed and dried alternately with water and ethanol before deposition.

7. The method for preparing the single-atom Ir-loaded Co3O4 material according to claim 3, characterized in that: The voltage of the constant potential deposition is set to -0.8 to -1.2 V, and the deposition time is 4 to 10 min.

8. The method for preparing the single-atom Ir-loaded Co3O4 material according to claim 3, characterized in that: During constant potential deposition and CV electrochemical treatment, the counter electrode was a platinum mesh and the reference electrode was a saturated calomel electrode.

9. The method for preparing the single-atom Ir-loaded Co3O4 material according to claim 3, characterized in that: The calcination temperature is 250-400°C, and the calcination time is 2-4h.

10. Use of the single-atom Ir-loaded Co3O4 material as claimed in claim 1 as an anode in an electrochemical chlorine production reaction.